The presence of psychological distress in healthcare workers across different care settings in Windsor, Ontario, during the COVID-19 pandemic: A cross-sectional study - Voth, Jennifer; Jaber, Lindsey; MacDougall, Linda; Ward, Leslee; Cordeiro, Jennifer; Miklas, Erica P. (Frontiers in Psychology, 2022)
Introduction: Few studies have examined psychological distress in healthcare workers (HCWs) across the care continuum. This study describes distress reported by HCWs across care settings and factors associated with distress. Methods: A cross-sectional survey of HCWs from Windsor, Ontario was conducted between May 30th, 2020 and June 30th, 2020. The survey included the Kessler Psychological Distress Scale (K10), sociodemographic, frontline status, perceptions of training, protection, support, respect among teams, and professional and personal stressors. Univariate analyses compared across settings and multivariate logistic regression assessed factors associated with distress. Results: 403 HCWs from hospital (49.4%), community health and social service (18.4%), first responder (14.7%), primary care (7.9%), home (6.0%), and long-term care (LTC; 4.0%) participated in the survey. Common concerns included fear of transmitting COVID-19 to family, safety on the job, and balancing personal care with work demands. LTC and home-care HCWs reported greater concern about workload and staffing, whereas community health workers were more anxious about their financial security. Overall, 228 (74.2%) HCWs who completed the K10 reported high distress, with greater rates among hospital and LTC HCWs. Distress was more likely in HCWs who identified as female, younger than 55, perceived lower respect among team, and experienced greater worry about physical and mental health and managing high workloads. Discussion. Results showed high degree of distress experienced by HCWs across care settings and the impact of the COVID-19 pandemic on personal and work-related stress. Promoting self-care and supportive and collaborative healthcare teams are promising avenues for mitigating symptoms of distress.